Patient confidentiality, the law and the healthcare records in the view of the PDPA 2010 - Zulhuda, Sonny (2014)
The enactment of Personal Data Protection Act (PDPA) 2010 has changed the industrial landscape of the maintenance and usage of the medical and healthcare records. The introduction of PDPA into the medical industry has also effectively shifted the conventional paradigm of looking “medical records” as the “doctor’s secrets” towards a more open and transparent notion of treating them as the “patient’s right” to his own personal data. The legislation has prescribed new statutory rights to patients as well as new statutory duties for the records holders concerning the entire lifecycle of medical records – commencing from the data collection to its usage, disclosure and disposal. On top of that, the processes in between involving data sharing, security and risk management would have to be fairly and lawfully managed. It is therefore understood that, contrary to the conventional practice and belief, the existing law of confidentiality are unable to protect patients’ personal data the same way as the PDPA does. It is not too much to say that all the medical records practitioners at all stages of process critically need to understand this law. With this background, the presenter will speak on two big parts: firstly he would explore the salient features of the PDPA 2010 and how it affects the current medical records framework and practices. Secondly, the presenter will engage the audience to look into practical matters such as the seven data protection principles, requirements of data protection standards, as well as risk management and due diligence steps towards compliance. The objective of having this understanding is to enable us achieve not only the compliance of PDPA in the management of medical records, but also to better safeguard the patients’ rights to data privacy and confidentiality.